2022
DOI: 10.1002/pei3.10090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of invasive Lantana camara on maize and cassava growth in East Usambara, Tanzania

Abstract: The impacts of invasive alien plant species on native plants are generally well documented, but little is known about the mechanisms underlying their impacts on crop growth. A better understanding of immediate as well as legacy effects and of direct and indirect impacts of invasive alien plant species is essential for an improved management of invaded cropland. We investigated how Lantana camara impacts the growth of two subsistence crops (maize and cassava) through competition for resources, allelopathy and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…summarizes the life history traits of the studied species. Few studies focus on the phenological interactions between natives and invasives in the same environmental conditions 74 . Phenological duration is a crucial factor in decoding the timing of individual species and gives us insight on the timing for introducing native species in the field 24 .…”
Section: Resultsmentioning
confidence: 99%
“…summarizes the life history traits of the studied species. Few studies focus on the phenological interactions between natives and invasives in the same environmental conditions 74 . Phenological duration is a crucial factor in decoding the timing of individual species and gives us insight on the timing for introducing native species in the field 24 .…”
Section: Resultsmentioning
confidence: 99%
“…A variety of compounds are involved in the process of allelopathy, which is often affected by numerous factors [15,16]. Many studies have shown that soil microorganisms alter the activity of allelochemicals in plants, and they can also alter the competitiveness of invasive plants in populations and communities [17][18][19][20]. Existing studies have focused on the degradation of toxic compounds into toxic allelochemicals by free-living microbial communities in the soil [19][20][21], the enhancement of plant tolerance to allelochemicals [22,23], and the expansion of the impact of allelochemicals by soil microorganisms through transfer networks in the soil [24].…”
Section: Introductionmentioning
confidence: 99%